Ethnobotany of plants used by indigenous communities in Birjand, a dry region with rich local traditional knowledge in eastern Iran - Mohammadi, Toktam; Moazzeni, Hamid; Pirani, Atefeh; Vaezi, Jamil; Motahhari, Khadijeh; Joharchi, Mohammad Reza; Bussmann, Rainer W. (Ethnobotany Research and Applications, 2023)
Background: Despite locating in a dry region with a mostly homogeneous ethnic group, South Khorassan province has a high diversity of medicinal plant uses and rich cultural background. The current study was conducted in Birjand (South Khorassan province) and its 18 adjacent villages to document information concerning the plants used and introduce important plant species using ethnobotanical indices. Methods: In total, 59 people were interviewed about local plants and their utilizations using a semi-structured questionnaire and personal observations between 2018 to 2020. All of the documented plants were collected and identified. The obtained data were analyzed using quantitative ethnobotanical indices. Results: A total of 119 plant species belonging to 93 families were identified. Asteraceae, Apiaceae, and Lamiaceae were the most used plant families. The most frequently plant part used was the aerial part. Decoction was reported as the most common preparation method. The highest UV and RFC values were recorded for Sclerorhachis leptoclada, Scrophularia leucoclada, and Nepeta saturejoides. The highest ICF was reported for digestive system disorders. 35 species showed fidelity level value of 100%. Conclusions: The present study reveals that the people in Birjand and the adjacent areas have a rich indigenous knowledge regarding the plants. Moreover, plants still maintain their place in people’s lives, especially as medicine and food. Older people were more knowledgeable than young ones. The results of this study can be used for screening plant species for future phytochemical and pharmacological studies. The present study will facilitate the protection programs of the endangered plants in Birjand area. Keywords: Conservation, Food, Medicinal plants, Pharmacology, Traditional knowledge